2020
DOI: 10.3390/md18080417
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptide TP4 Targets Mitochondrial Adenine Nucleotide Translocator 2

Abstract: Tilapia piscidin (TP) 4 is an antimicrobial peptide derived from Nile tilapia (Oreochromis niloticus), which shows broad-spectrum antibacterial activity and excellent cancer-killing ability in vitro and in vivo. Like many other antimicrobial peptides, TP4 treatment causes mitochondrial toxicity in cancer cells. However, the molecular mechanisms underlying TP4 targeting of mitochondria remain unclear. In this study, we used a pull-down assay on A549 cell lysates combined with LC-MS/MS to discover that TP4 targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
(119 reference statements)
1
2
0
Order By: Relevance
“…TP4 was previously found to preferentially bind to mitochondria and the mitochondrial membrane protein, adenine nucleotide translocase 2, in non-small cell lung cancer cells and triple-negative breast cancer cells [25,39]. In the present study, we demonstrated that TP4 induces mitochondrial hyperpolarization in synovial sarcoma cells.…”
Section: Discussionsupporting
confidence: 68%
“…TP4 was previously found to preferentially bind to mitochondria and the mitochondrial membrane protein, adenine nucleotide translocase 2, in non-small cell lung cancer cells and triple-negative breast cancer cells [25,39]. In the present study, we demonstrated that TP4 induces mitochondrial hyperpolarization in synovial sarcoma cells.…”
Section: Discussionsupporting
confidence: 68%
“…On the one hand, the change in mitochondrial membrane potential will cause the abnormal continuous opening of the MPTP [ 38 ]. On the other hand, AMPs affect the opening of the MPTP by regulating the production of ROS, the concentration of Ca 2+ , or targeting the MPTP components [ 44 ]. Because MPTP spans the outer and inner membranes of mitochondria, it must also affect MOMP and MIMP [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ting et al [ 99 ] showed that O. niloticus ’s piscidin-4 peptide (TP4: FFRHLFRGAKAIFRGARQGXRAHKVVSRYRNRDVPETDNNQEEP [ 100 ]), endowed with a amphiphilic α-helical conformation structure and belonging to an antimicrobial peptide family first identified by Chinchar et al [ 101 ] in the mast cells of the hybrid striped bass ( Morone saxatilis × Morone chrysops ), exerted a microtubule-destabilizing activity, which could be the mechanistic requirement for the TP4-mediated death of A549 lung carcinoma cells. Additional studies have demonstrated that the peptide was also active on triple-negative breast cancer cells, glioblastoma cells and SW982 human synovial sarcoma cells [ 102 , 103 , 104 , 105 , 106 , 107 ]. The data reported for synovial tumor cells indicated the promotion of necrosis via the induction of calcium overload, mitochondrial hyperpolarization, ROS accumulation and impairment of the antioxidant defense.…”
Section: Marine Animals As Sources Of Anticancer Peptides: In Vitro E...mentioning
confidence: 99%